A Book of Poems in Internet Space: an Intermedial Aspect - E. A. Abrosimova; Yu. D. Kravchenko (Научный диалог)
The work was carried out in line with the current idea of the Internet as a global media that interacts with various sign systems and influences the structural and compositional features of the verbal text. The relevance of the study is due to the formation of the concept of intermediality in the context of a new cultural direction, called “metavirtualism”. The aim of the article is to characterize the principles underlying the structure and composition of the network poetic “book”. Russian-language poetic cycles are considered, the structural and compositional features and expressive means of which are associated with Internet technologies. Such aspects as the type of intermediality and ways of organizing the structure and composition of the network “book” are analyzed; the reader’s way of getting acquainted with the work and the degree of freedom of this way; manifestation of the category of ephemerality. It is concluded that technological poetry, paradoxically, strengthens traditional book forms, but also has an independent value, visualizing poetic images and metaphors. Internet technologies can be “embedded” into the structure and composition of a poetry book at various levels: it can be relative autonomy; interaction at the level of a conceptual metaphor explicated with the help of Internet media (Google maps); almost complete fusion of media.